Interaction between pathogenic ganoderma isolates and fungi of suppressive soil - Mohamad Rizuan, Sarbini (Universiti Malaysia Sarawak (UNIMAS), 2013)
Genus Ganoderma is a well-known fungal pathogen to many plants including to the most important commodity crop in Malaysia, oil palm. Although several strategies have been developed to control Ganoderma–induced diseases, the methods are still less effective. Many laboratory and in control environment studies indicate very good and promising results in controlling Ganoderma disease, but these do not happen when applied in a field. Interaction characteristics of Ganoderma with its different isolates and with soils microbes could possibly explain the success of the fungus to grow and to develop disease on the infected plant. In this study the interactions between isolates of pathogenic Ganoderma and between the isolates of Ganoderma and fungi from suppressive soil made with twenty five isolates of Ganoderma collected from different infected oil palm and ornamental palm trees. The tested isolates were arranged in pairs on Malt Extract Agar (MEA) and incubated in growth chamber in the dark 25  2OC. In an experiment of interactions between the Ganoderma isolates, six types of interactions were observed. They were: (a) formation zone of sparse mycelia, (b) barrage formation of mycelia, (c) barrage formation with pigment zone of mycelia, (d) overgrown of one isolate by another paired isolate, (e) formation of clearing zone between the two isolates and (f) the intermingled of mycelia between the paired isolates to homogenous colony. All of the 294 pairings Ganoderma isolates showed incompatible interactions, except 31 pairings of the different isolates obtained from ornamental palms and identical isolates from oil palm. Growth of the Ganoderma on Carboxymethylcellulose Agar (CMC), Starch Agar (SA), Yeast Phosphate Soluble Starch (YPSS), Yeast Phosphate Agar (YEA) and Lipase Agar (LiA) were also studied to determine the ability of Ganoderma to utilize cellulose, starch and lignin. All of the Ganoderma isolates were able to grow on the media. However, in general isolates S2K8 and K1K5 were among the faster growing isolates on CMC, YPSS, SA and LiA while isolate Sop2 was on YEA. Because of the good growth on all the tested media, isolates S2K8 and K1K5 were chosen to be paired with 104 isolates of fungi (suppressive soil). It was found that many of the tested isolates from soil were overgrown by these two Ganoderma isolates except for twelve isolates, which included Pennicilium sp. 2, Nerospora sp., Schizophylum commune 1 and 2, Aspergillus sp. 1, Basidomycets 6, Trichoderma sp. 3, Trichoderma sp. 4, Trichoderma sp. 5, Trichodrma sp. 6, Trichoderma sp. 7 and Trichoderma harzianum. These twelve isolates formed barrage or zone of sparse mycelia when grown together with S2K8 and K1K5 Ganoderma isolates. These soil fungi isolates except, T. harzianum however did not grow in Malt Extract Broth (MEB) that contained 7-day-old Ganoderma incubated at 25  2OC. Growth of T. harzianum was significantly inhibited on MEA incorporated with 2.50 g/ml crude extract of S2K8, K1K5 and S1K4 isolates. In the present study, metabolites of S2K7, Kabuloh 1 and KB 1 were also extracted but they were not tested in this inhibition experiment because of the limited amount of the materials. The crude extracts of Ganoderma isolates were further analyzed to determine the present of triterpenes group. Amongst the triterpenes group components that were detected from the tested Ganoderma were of Ganoderic Acid  and Ganoderic Acid which were the highest produced by the S2K8 and K1K5, respectivelyGanoderic Acid G and Ganoderic A6 were also produced by all the tested Ganoderma isolates with the highest producers was by S1K4 and S2K7, respectively. The findings of the present study indicate that the growth of pathogenic Ganoderma species were able to inhibit the growth of fungi in suppressive soil by physical and metabolite interactions. This is a possible reason why the Ganoderma disease can occur in many plants and thus difficult to control. In future, more studies are needed especially to investigate the characteristics of pathogenic Ganoderma metabolites and effect of other components of fungal metabolites on other fungi in nature.